2022
DOI: 10.1038/s41598-022-23665-0
|View full text |Cite
|
Sign up to set email alerts
|

A formula to improve the reliability of optical axial length measurement in IOL power calculation

Abstract: To verify the influence of axial length (AL) variations after cataract surgery in IOL power calculation. Patients underwent ophthalmic evaluation before surgery, including optical biometry with IOLMaster 500. Same exams were repeated 2 months after surgery: AL of operated eye was evaluated using two modes (pseudophakic/aphakic options). Mean Keratometry and AL changes were analyzed. Furthermore, refractive prediction error (PE) was back-calculated with Barrett Universal-II, Hoffer-Q, Holladay-1 and SRK/T formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 41 publications
(58 reference statements)
0
37
0
Order By: Relevance
“…We are aware that axial length measurements are not very precise and some corrections are needed, but they should be precise enough for checking relationships. 4 Dove Medical Press encourages responsible, free and frank academic debate. The contentTxt of the Clinical Ophthalmology 'letters to the editor' section does not necessarily represent the views of Dove Medical Press, its officers, agents, employees, related entities or the Clinical Ophthalmology editors.…”
Section: Dear Editormentioning
confidence: 99%
“…We are aware that axial length measurements are not very precise and some corrections are needed, but they should be precise enough for checking relationships. 4 Dove Medical Press encourages responsible, free and frank academic debate. The contentTxt of the Clinical Ophthalmology 'letters to the editor' section does not necessarily represent the views of Dove Medical Press, its officers, agents, employees, related entities or the Clinical Ophthalmology editors.…”
Section: Dear Editormentioning
confidence: 99%
“…Biometry is indispensable for the diagnosis and treatment of ophthalmic diseases. Keratometry (K), axial length (AL), and anterior chamber depth (ACD) are important variables in the initial intraocular lens (IOL) calculation formulas [ 1 3 ]. Newer algorithms such as the Holladay 2 and Barrett Universal II formulas also use corneal diameter (CD) and lens thickness (LT) to improve accuracy [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, De Bernardo et al recently reported that cataract can modify the lens refractive index, and this could alter AL obtained by biometers using the group refractive index. 2 On these bases, they proposed a correction factor to improve the reliability of AL measurement, applicable to the entire range of AL. This corrected AL (ALc) can eliminate any systematic error resulting from the biometer.…”
mentioning
confidence: 99%